PERILAKU KONSUMEN BELANJA ONLINE DI SOLID FASHION – SHOPPE PASCA PANDEMI COVID - Lianto, Theresia Dharma (Seminar Nasional Ilmu Terapan, 2024)
This thesis research is about online shopping consumer behavior at Solid Fashion - Shoppe after the Covid pandemic. This thesis discusses the beginning of the emergence of Covid which was so dangerous that people were afraid to leave the house and chose to shop online. Online shopping was the best solution at that time so that sales in the Solid Fashion Shoppe Online Store increased rapidly, but as time goes by, 2023 will enter the new normal era so there are several people who are already carrying out activities as before, so sales in the Online Store Solid Fashion is declining. So through this research, researchers want to know what things buyers consider when deciding to purchase in 2020 so that sales in 2023 can be stable or increase. This research uses a qualitative descriptive research method. The data collection technique used was through interviews with 6 selected sources who met the criteria determined by the researcher. In this research, the data obtained from interviews is presented in in-depth descriptive form with the result that there are 4 things that buyers consider when deciding to purchase, namely: price changes, differences in offers, personal needs, psychological conditions.